A method and material for detecting alcohol concentration
By processing micro-nano structures on the surface of polydimethylsiloxane or polytetrafluoroethylene films, measuring the contact angle of alcohol, combined with the alcohol concentration-contact angle diagram, the rapid and accurate detection of alcohol concentration is achieved, and the problems of expensive equipment, complex operation and long-term consumption in the existing methods are solved.
Patent Information
- Application Number
- CN202210367513.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-04-08
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2042-04-08
AI Technical Summary
The existing alcohol concentration detection methods have problems such as expensive equipment, complex operation and long-term use.
Provided a method comprising processing a micro-nano structure on the surface of a polydimethylsiloxane film or a polytetrafluoroethylene film, reading the concentration of alcohol by measuring the contact angle of alcohol on the surface of the substrate material, in combination with the alcohol concentration-contact angle map.
This method is simple to operate, saves detection solvents, takes a short time, and the surface of the substrate material after laser processing has superhydrophobic and super alcohol-friendly characteristics, which improves the accuracy of alcohol concentration detection.
Smart Images

Figure CN114720501B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of alcohol concentration detection, and in particular to a method and material for detecting alcohol concentration. Background Art
[0002] Alcohol is an important chemical reagent, and different concentrations of alcohol often have different uses. Anhydrous ethanol can be used for dehydration, 75% alcohol can be used for disinfection, and 30% alcohol can be used for physical cooling. In the field of fine chemical synthesis, the concentration of ethanol is also the key to chemical reactions. Therefore, the determination of alcohol concentration is very important.
[0003] There are many methods for detecting alcohol concentration at present, the more typical ones are density bottle method, alcohol meter method, gas chromatography, etc. Among them, the density bottle method has high accuracy, but the operation is cumbersome and the analysis time is long; the alcohol meter method is simple and fast to operate, but it is easily affected by other non-ethanol components and ambient temperature; the gas chromatography method has high detection sensitivity and fast analysis speed, but the detection cost is relatively high.
[0004] In summary, there are many methods for detecting alcohol concentration at present, but these methods have disadvantages such as expensive equipment, complex operation, long time consumption and large sample size.
[0005] In view of this, it is necessary to propose a method for detecting alcohol concentration and a material thereof to solve the above-mentioned defects. Summary of the invention
[0006] The main purpose of the present invention is to provide a method and material for detecting alcohol concentration, aiming to solve the problems of expensive equipment, complicated operation and long time consumption in the existing alcohol concentration detection method. To achieve the above purpose, the present invention provides a method for detecting alcohol concentration, the method comprising the steps: S1, providing a substrate material, processing a micro-nano structure on the surface of the substrate material, the substrate material is one selected from polydimethylsiloxane film or polytetrafluoroethylene film; S2, taking a plurality of alcohols of known concentrations and dropping them on the surface of the substrate material one by one, respectively measuring the contact angles corresponding to the known concentrations of alcohol, and making an alcohol concentration-contact angle diagram; S3, dropping alcohol of unknown concentration on the surface of the substrate material, and measuring the contact angle of the alcohol on the substrate material; S4, reading the concentration of the alcohol according to the contact angle and the alcohol concentration-contact angle diagram.
[0007] Preferably, the step S3 further comprises repeatedly measuring the contact angle and taking an average value of multiple contact angle values.
[0008] Preferably, the processing method adopts laser processing, and the laser processing method includes: focusing a laser beam on the surface of the base material, and processing the surface of the base material by laser direct writing.
[0009] Preferably, the base material is the polydimethylsiloxane film, the repetition frequency of the laser processing is 50-200kHz, the pulse width of the laser processing is 350fs, the wavelength of the laser processing is 1035nm, the processing speed of the laser processing is 10-200mm / s, and the output power of the laser processing is 1-2W.
[0010] Preferably, the base material is the polytetrafluoroethylene film, the repetition frequency of the laser processing is 50-200kHz, the pulse width of the laser processing is 350fs, the wavelength of the laser processing is 1035nm, the processing speed of the laser processing is 10-200mm / s, and the output power of the laser processing is 2-5W.
[0011] Preferably, the size of the micro-nano structure is 8 to 20 micrometers.
[0012] The present invention also provides a material for detecting alcohol concentration, comprising a substrate material with a micro-nano structure prepared by the above method.
[0013] Compared with the prior art, the method and material for detecting alcohol concentration provided by the present invention have the following beneficial effects:
[0014] The present invention provides a method and material for detecting alcohol concentration, the method comprising the following steps: S1, providing a substrate material, processing a micro-nano structure on the surface of the substrate material, the substrate material being one selected from a polydimethylsiloxane film or a polytetrafluoroethylene film; S2, taking a plurality of alcohols of known concentrations and dropping them one by one on the surface of the substrate material, respectively measuring the contact angles corresponding to the alcohols of known concentrations, and making an alcohol concentration-contact angle diagram; S3, dropping alcohol of unknown concentration on the surface of the substrate material, and measuring the contact angle of the alcohol on the substrate material; S4, reading the alcohol concentration according to the contact angle and the alcohol concentration-contact angle diagram. The present invention can identify the alcohol concentration according to the size of the alcohol contact angle on its surface by processing a micro-nano structure on the surface of the substrate material, the preparation of the substrate material is convenient and fast, the cost is low, and the method for detecting the alcohol concentration is simple to operate, saves detection solvent, and takes less time. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the structures shown in these drawings without paying creative work.
[0016] Figure 1 : are scanning electron microscope images of the surface of the substrate material in one embodiment of the present invention, wherein a is a scanning electron microscope image of the surface of the polydimethylsiloxane film after laser processing, and b is a scanning electron microscope image of the surface of the polytetrafluoroethylene film after laser processing;
[0017] Figure 2 : is a contact angle diagram of the surface of the polydimethylsiloxane film material in one embodiment of the present invention, wherein a is a water contact angle diagram of the polydimethylsiloxane film before laser processing, b is a contact angle diagram of the polydimethylsiloxane film before laser processing with an alcohol concentration of 100%, c is a water contact angle diagram of the polydimethylsiloxane film after laser processing, and d is a contact angle diagram of the polydimethylsiloxane film after laser processing with an alcohol concentration of 100%;
[0018] Figure 3 : is a contact angle diagram of the surface of the polytetrafluoroethylene film material in one embodiment of the present invention, a is a water contact angle diagram of the surface of the polytetrafluoroethylene film before laser processing, b is a contact angle diagram of 100% alcohol on the surface of the polytetrafluoroethylene film before laser processing, c is a water contact angle diagram of the polytetrafluoroethylene film after laser processing, and d is a contact angle diagram of 100% alcohol on the surface of the polytetrafluoroethylene film after laser processing;
[0019] Figure 4 1 is an alcohol concentration-contact angle diagram of a polydimethylsiloxane film in an embodiment of the present invention, wherein a is an alcohol concentration-contact angle diagram of the polydimethylsiloxane film before laser processing, and b is an alcohol concentration-contact angle diagram of the polydimethylsiloxane film after laser processing;
[0020] Figure 5 1 is an alcohol concentration-contact angle diagram of a polytetrafluoroethylene film in an embodiment of the present invention, a is an alcohol concentration-contact angle diagram of a polytetrafluoroethylene film before laser processing, and b is an alcohol concentration-contact angle diagram of a polytetrafluoroethylene film after laser processing;
[0021] Figure 6 is a schematic diagram of a laser processing device in one embodiment of the present invention;
[0022] Description of Figure Numbers:
[0023] Laser 1; laser beam 2; first reflector 3; beam expander 4; second reflector 5; galvanometer 6; processing platform 7; sample to be processed 8; computer 9.
[0024] The purpose, features and advantages of the present invention will be further described with reference to the accompanying drawings in conjunction with the embodiments. DETAILED DESCRIPTION
[0025] It should be understood that the specific embodiments described herein are only used to explain the present invention, and are not used to limit the present invention.
[0026] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0027] It should be noted that all directional indications in the embodiments of the present invention (such as up, down, left, right, front, back, etc.) are only used to explain the relative position relationship, movement status, etc. between the components under a certain specific posture (as shown in the accompanying drawings). If the specific posture changes, the directional indication will also change accordingly.
[0028] In addition, the descriptions of "first", "second", etc. in the present invention are only used for descriptive purposes and cannot be understood as indicating or implying their relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features. In addition, the technical solutions between the various embodiments can be combined with each other, but they must be based on the ability of ordinary technicians in the field to implement them. When the combination of technical solutions is contradictory or cannot be implemented, it should be deemed that such a combination of technical solutions does not exist and is not within the scope of protection required by the present invention.
[0029] Please refer to the attached Figures 1 to 6 The present invention provides a method for detecting alcohol concentration and a material thereof, the method comprising the steps of: S1, providing a substrate material, processing a micro-nano structure on the surface of the substrate material, the substrate material being one selected from a polydimethylsiloxane film or a polytetrafluoroethylene film; S2, taking a plurality of alcohols of known concentrations and dropping them on the surface of the substrate material one by one, respectively measuring the contact angles corresponding to the known concentrations of alcohol, and making an alcohol concentration-contact angle diagram; S3, dropping alcohol of unknown concentration on the surface of the substrate material, and measuring the contact angle of the alcohol on the substrate material; S4, reading the concentration of the alcohol according to the contact angle and the alcohol concentration-contact angle diagram.
[0030] Specifically, in step S1, a micro-nano structure is processed on the surface of the base material, and the surface of the processed base material exhibits super-hydrophobic and super-alcoholophilic properties. The base material can be a polydimethylsiloxane film or a polytetrafluoroethylene film. The cost of the base material is relatively low, and the processed polydimethylsiloxane film and polytetrafluoroethylene film both have super-alcoholophilic properties, which is convenient for better detection of alcohol concentration.
[0031] It should be understood that the processing method can be selected according to actual needs, including but not limited to one or more of laser processing, traditional mechanical processing or chemical preparation process.
[0032] Specifically, in this embodiment, the processing method adopts laser processing, and the laser processing method includes: focusing a laser beam on the surface of the substrate material, processing the surface of the substrate material by laser direct writing, and processing the micro-nano structure, the size of the micro-nano structure is 8 to 20 microns. The specific structure and type of the laser processing device can be set according to actual needs, please refer to the attached Figure 6 In this embodiment, a laser processing device is used, including a laser 1, a laser beam 2, a first reflector 3, a beam expander 4, a second reflector 5, a galvanometer 6, a processing platform 7, a sample to be processed 8 and a computer 9. The laser 1, the first reflector 3, the second reflector 5, the processing platform 7 and the computer 9 are placed in the same plane in sequence, and the galvanometer 6 is located above the processing platform 7. The method of using the device is that the laser beam 2 first comes out of the laser 1, passes through the first reflector 3, the beam expander 4 and the second reflector 5 in turn, enters the galvanometer 6, and finally focuses on the surface of the sample to be processed 8. The processed graphics and parameters such as energy frequency are drawn and set by the computer 9.
[0033] It should be understood that the laser processing parameters can be adjusted according to the actual situation and the selected materials. In a specific example, the base material is polydimethylsiloxane film, and laser processing is used. The range of laser processing parameters can be selected as follows: repetition frequency of 50 to 200 kHz, pulse width of 350 fs, wavelength of 1035 nm, processing speed of 10 to 200 mm / s, and output power of 1 to 2 W.
[0034] In another specific example, polytetrafluoroethylene film is selected as the base material and laser processing is used. The range of laser processing parameters can be selected as follows: repetition frequency is 50-200kHz, pulse width is 350fs, wavelength of the laser processing is 1035nm, processing speed is 10-200mm / s, output power is 2-5W.
[0035] Please see attached Figure 1 , Figure 1-a is a scanning electron microscope image of the surface of a polydimethylsiloxane film material in an embodiment, wherein the laser processing parameters are: pulse width 350fs, repetition frequency 100KHz, central wavelength 1035nm, output power 2W, scanning interval 15μm, processing speed 150mm / s. Before laser processing, the surface of the polydimethylsiloxane film is relatively smooth. After laser processing, Figure 1 -a shows that a micro-nano structure is processed on the surface of the polydimethylsiloxane film. The size of the micro-nano structure is 8-20μm, and the micro-nano structure is composed of multiple micro-scale coral-like structures.
[0036] In detail, Figure 1 -b is a scanning electron microscope image of the surface of a polytetrafluoroethylene film material in an embodiment, wherein the laser processing parameters are: pulse width 350fs, pulse repetition frequency 100KHz, central wavelength 1035nm, output power 5W, scanning spacing 15μm, processing speed 100mm / s. Before laser processing, the surface of polytetrafluoroethylene is relatively flat. After laser processing, Figure 1 -b shows that micro-nano structures are processed on the surface of polytetrafluoroethylene. The size of the micro-nano structures is 2 to 15 μm, and the micro-nano structures are composed of multiple micro-scale coral-like structures.
[0037] Please refer to the attached Figure 2 and 3 Still using the above specific embodiment to illustrate, before laser processing, the surface of the polydimethylsiloxane film exhibits hydrophobic and alcoholophilic properties, with a water contact angle (WCA) of 96.7° and a contact angle (ACA) of 100% alcohol of 22.8°; after laser processing, the surface of the polydimethylsiloxane film exhibits super-hydrophobic and super-alcoholophilic properties, with a water contact angle of 164.6° and a contact angle of 100% alcohol of 2.6°.
[0038] At the same time, for polytetrafluoroethylene film materials, before laser processing, the surface of the polytetrafluoroethylene film exhibited hydrophobic and alcoholic properties, with a water contact angle of 91.2° and a contact angle of 100% alcohol of 19.5°; after laser processing, the surface of the polytetrafluoroethylene film exhibited superhydrophobic and superalcoholic properties, with a water contact angle of 157.8° and a contact angle of 100% alcohol of 3.8°.
[0039] From the above, it can be seen that the surface of the processed substrate material shows super-hydrophobic and super-alcohol-philic properties, which provides good conditions for detecting alcohol concentration, makes the contact angle corresponding to the alcohol concentration have a large degree of differentiation, is easy to identify, and can better detect the alcohol concentration with higher accuracy.
[0040] In step S2, after the substrate material is processed into a micro-nano structure, an alcohol concentration-contact angle diagram of the processed substrate material is drawn. A plurality of alcohols of different concentrations are dropped on the surface of the substrate material, the contact angle corresponding to each concentration is measured, and the alcohol concentration-contact angle diagram is drawn. In addition, more alcohols of different concentrations can be tested to obtain a plurality of different contact angle values. At the same time, the contact angle of each alcohol concentration can be repeatedly measured, and the average value of the contact angle is taken, so that the drawing of the alcohol concentration-contact angle diagram is more precise and the measurement of the alcohol concentration is more accurate.
[0041] In step S3, an alcohol of unknown concentration is taken and dripped on the surface of the base material to measure its contact angle. The method of measuring the contact angle can be selected according to actual needs. A contact angle meter can be used for measurement, or photos can be taken and measured using computer software. The operation is simple and the cost is low. The step of measuring the contact angle can also be repeated multiple times. The alcohol of unknown concentration is dripped multiple times, multiple contact angles are measured, and the average of the multiple contact angle values is taken to make the measurement result more accurate.
[0042] In step S4, after the contact angle is measured, the corresponding alcohol concentration value is read according to the alcohol concentration-contact angle diagram of the base material that has been drawn, so as to obtain a relatively accurate alcohol concentration value.
[0043] Please refer again to the attached Figure 4 and attached Figure 5 , still using the above specific embodiment to illustrate, the wettability of different alcohol concentrations on the surface of polydimethylsiloxane film or polytetrafluoroethylene film was studied by a high temperature wetting angle measuring instrument. For polydimethylsiloxane film, the contact angles of alcohol with alcohol concentrations of 20%, 40%, 60%, 80%, and 100% on the surface of polydimethylsiloxane film before laser processing were 82.0°, 63.4°, 56.7°, 46.3°, and 22.8°, respectively. The contact angles of alcohol with alcohol concentrations of 20%, 40%, 60%, 80%, and 100% on the surface of polydimethylsiloxane film after laser processing were 155.5°, 132.4°, 10.5°, 2.2°, and 2.6°, respectively.
[0044] In detail, for the polytetrafluoroethylene film, the contact angles of alcohol with concentrations of 20%, 40%, 60%, 80%, and 100% on the surface of the polytetrafluoroethylene film before laser processing are 71.4°, 59.5°, 51.7°, 42.0°, and 19.5°, respectively; the contact angles of alcohol with concentrations of 20%, 40%, 60%, 80%, and 100% on the surface of the polytetrafluoroethylene film after laser processing are 158.8°, 143.3°, 108.5°, 2.1°, and 3.8°, respectively.
[0045] The surfaces of laser-processed polydimethylsiloxane film and polytetrafluoroethylene film both have superwetting properties, and different concentrations of alcohol have different surface tensions. Droplets with different surface tensions have different static contact angles on superwetting surfaces. On this basis, the alcohol concentration can be easily and quantitatively determined.
[0046] It should be noted that the base material can be reused, so for the same base material, the alcohol concentration-contact angle diagram only needs to be prepared once, and the same material and the corresponding alcohol concentration-contact angle diagram can be reused for subsequent measurements of unknown alcohol concentrations. The preparation method of the base material is simple, the method of measuring the contact angle is simple and quick, and the method of deriving the alcohol concentration from the corresponding alcohol concentration-contact angle diagram is simple and efficient, and saves the detection solution.
[0047] The above results show that the surface of the substrate material with micro-nano structure after laser processing can identify the alcohol concentration according to the size of the contact angle. It is simple and efficient, saves detection solvent, and the preparation of the substrate material is convenient and quick.
[0048] The present invention also provides a material for detecting alcohol concentration, comprising a substrate material with a micro-nano structure prepared by the above method.
[0049] The present invention will be further described below in conjunction with examples, but the present invention is not limited to the following examples.
[0050] Example 1
[0051] (1) Providing a polydimethylsiloxane film material with a thickness of 0.3 mm, the water contact angle of which is 96.7° and the alcohol contact angle of which is 22.8°;
[0052] (2) Using a laser processing method, a micro-nano structure was processed on the surface of a polydimethylsiloxane film by laser direct writing; the water contact angle after processing was 164.6°, and the alcohol contact angle was 2.6°; wherein the laser processing parameters were: pulse width 350fs, pulse repetition frequency 100KHz, central wavelength 1035nm, output power 2W, scanning spacing 15μm, and processing speed 150mm / s;
[0053] (3) Take a drop of 25% alcohol and drop it on the surface of the processed polydimethylsiloxane film. Use a high temperature wetting angle meter to measure the contact angle to be 145.7°;
[0054] (4) Figure 4 -b, according to the alcohol concentration-contact angle diagram, the contact angle of 145.7° corresponds to an alcohol concentration of 28.5%, which has an error of 3.5% from the actual alcohol concentration.
[0055] Example 2
[0056] (1) Providing a polydimethylsiloxane film material with a thickness of 0.3 mm, the water contact angle of which is 96.7° and the alcohol contact angle of which is 22.8°;
[0057] (2) Using a laser processing method, a micro-nano structure was processed on the surface of a polydimethylsiloxane film by laser direct writing; the water contact angle after processing was 164.6°, and the alcohol contact angle was 2.6°; wherein the laser processing parameters were: pulse width 350fs, pulse repetition frequency 100KHz, central wavelength 1035nm, output power 2W, scanning spacing 15μm, and processing speed 150mm / s;
[0058] (3) Take a 50% alcohol and drop it on the surface of the processed polydimethylsiloxane film. Use a high temperature wetting angle meter to measure the contact angle to be 36.9°;
[0059] (4) Figure 4 -b, according to the alcohol concentration-contact angle diagram, the contact angle of 36.9° corresponds to an alcohol concentration of 55.7%, which has an error of 5.7% from the actual alcohol concentration.
[0060] Example 3
[0061] (1) Providing a polydimethylsiloxane film material with a thickness of 0.3 mm, the water contact angle of which is 96.7° and the alcohol contact angle of which is 22.8°;
[0062] (2) Using a laser processing method, a micro-nano structure was processed on the surface of a polydimethylsiloxane film by laser direct writing; the water contact angle after processing was 164.6°, and the alcohol contact angle was 2.6°; wherein the laser processing parameters were: pulse width 350fs, pulse repetition frequency 100KHz, central wavelength 1035nm, output power 2W, scanning spacing 15μm, and processing speed 150mm / s;
[0063] (3) Take a drop of 75% alcohol and drop it on the surface of the processed polydimethylsiloxane film. Use a high temperature wetting angle meter to measure the contact angle to be 7.4°;
[0064] (4) Figure 4 -b, according to the alcohol concentration-contact angle diagram, the contact angle of 7.4° corresponds to an alcohol concentration of 67.5%, which has an error of 7.5% from the actual alcohol concentration.
[0065] Example 4
[0066] (1) providing a polytetrafluoroethylene film with a thickness of 0.2 mm, a water contact angle of 91.2°, and an alcohol contact angle of 19.5°;
[0067] (2) Using a laser processing method, a micro-nano structure was processed on the surface of a polytetrafluoroethylene film by laser direct writing; the water contact angle after processing was 157.8°, and the alcohol contact angle was 3.8°; wherein the laser processing parameters were: pulse width 350fs, pulse repetition frequency 100KHz, central wavelength 1035nm, output power 5W, scanning spacing 15μm, and processing speed 100mm / s;
[0068] (3) Take a drop of 25% alcohol and drop it on the surface of the processed polytetrafluoroethylene film. Use a high temperature wetting angle meter to measure the contact angle to be 151.9°;
[0069] (4) Figure 5 -b, according to the alcohol concentration-contact angle diagram, the contact angle of 151.9° corresponds to an alcohol concentration of 29%, which has an error of 4% from the actual alcohol concentration.
[0070] Example 5
[0071] (1) providing a polytetrafluoroethylene film with a thickness of 0.2 mm, a water contact angle of 91.2°, and an alcohol contact angle of 19.5°;
[0072] (2) Using a laser processing method, a micro-nano structure was processed on the surface of a polytetrafluoroethylene film by laser direct writing; the water contact angle after processing was 157.8°, and the alcohol contact angle was 3.8°; wherein the laser processing parameters were: pulse width 350fs, pulse repetition frequency 100KHz, central wavelength 1035nm, output power 5W, scanning spacing 15μm, and processing speed 100mm / s;
[0073] (3) Take 50% alcohol and drop it on the surface of the processed polytetrafluoroethylene film. Use a high temperature wetting angle meter to measure the contact angle to be 128.4°;
[0074] (4) Figure 5 -b, according to the alcohol concentration-contact angle diagram, the contact angle of 128.4° corresponds to an alcohol concentration of 48.6%, which has an error of 1.4% from the actual alcohol concentration.
[0075] Example 6
[0076] (1) providing a polytetrafluoroethylene film with a thickness of 0.2 mm, a water contact angle of 91.2°, and an alcohol contact angle of 19.5°;
[0077] (2) Using a laser processing method, a micro-nano structure was processed on the surface of a polytetrafluoroethylene film by laser direct writing; the water contact angle after processing was 157.8°, and the alcohol contact angle was 3.8°; wherein the laser processing parameters were: pulse width 350fs, pulse repetition frequency 100KHz, central wavelength 1035nm, output power 5W, scanning spacing 15μm, and processing speed 100mm / s;
[0078] (3) Take a drop of 75% alcohol and drop it on the surface of the processed polytetrafluoroethylene film. Use a high temperature wetting angle meter to measure the contact angle to be 46.8°;
[0079] (4) Figure 5 -b, according to the alcohol concentration-contact angle diagram, the contact angle of 128.4° corresponds to an alcohol concentration of 71.6%, which has an error of 3.4% from the actual alcohol concentration.
[0080] In summary, after verification, it can be seen that this method has a small error in detecting alcohol concentration and the measurement results are more accurate.
[0081] The above are only preferred embodiments of the present invention, and are not intended to limit the patent scope of the present invention. Any equivalent structure or equivalent process transformation made using the contents of the present invention specification and drawings, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.
Claims
1. A method for detecting alcohol concentration, characterized in that: The method comprises the steps of: S1, providing a base material, processing a micro-nano structure on the surface of the base material, wherein the base material is one selected from a polydimethylsiloxane film or a polytetrafluoroethylene film; The processing method adopts laser processing, and the laser processing method includes: focusing a laser beam on the surface of the base material, and processing the surface of the base material by laser direct writing; The substrate material is the polydimethylsiloxane film, the repetition frequency of the laser processing is 50-200kHz, the pulse width of the laser processing is 350fs, the wavelength of the laser processing is 1035nm, the processing speed of the laser processing is 10-200mm / s, and the output power of the laser processing is 1-2W, or the substrate material is the polytetrafluoroethylene film, the repetition frequency of the laser processing is 50-200kHz, the pulse width of the laser processing is 350fs, the wavelength of the laser processing is 1035nm, the processing speed of the laser processing is 10-200mm / s, and the output power of the laser processing is 2-5W; S2, taking a plurality of alcohols of known concentrations and dropping them one by one on the surface of the base material, respectively measuring the contact angles corresponding to the alcohols of known concentrations, and making an alcohol concentration-contact angle graph; S3, adding alcohol of unknown concentration to the surface of the base material, and measuring the contact angle of the alcohol on the base material; S4, reading the alcohol concentration according to the contact angle and the alcohol concentration-contact angle graph.
2. The method for detecting alcohol concentration according to claim 1, characterized in that: The step S3 also includes repeatedly measuring the contact angle and taking an average value of multiple contact angle values.
3. The method for detecting alcohol concentration according to claim 1, characterized in that: The size of the micro-nano structure is 8 to 20 microns.
4. A material for detecting alcohol concentration, characterized in that: The invention comprises a substrate material having a micro-nano structure prepared by the method according to any one of claims 1 to 3.
Citation Information
Patent Citations
Alcohol concentration measuring device utilizing graphene terahertz surface plasma effect and method thereof
CN106442424A
Liquid detection sensor, detection object, and liquid detection system
JP2021038971A